If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(1-2x)=-6(x+8)
We move all terms to the left:
6(1-2x)-(-6(x+8))=0
We add all the numbers together, and all the variables
6(-2x+1)-(-6(x+8))=0
We multiply parentheses
-12x-(-6(x+8))+6=0
We calculate terms in parentheses: -(-6(x+8)), so:We get rid of parentheses
-6(x+8)
We multiply parentheses
-6x-48
Back to the equation:
-(-6x-48)
-12x+6x+48+6=0
We add all the numbers together, and all the variables
-6x+54=0
We move all terms containing x to the left, all other terms to the right
-6x=-54
x=-54/-6
x=+9
| X2+8x+16=36 | | 4n+2(5)n=$585 | | 7p+3(6+p)=88 | | 4y/3-7=2/5 | | 10−3m=-11 | | 8m+-1m+-3m=+5 | | -4-9z=8-2z-9z | | 8(4-4b)+3=131 | | y=2(2-1)+5 | | 74=6w+2 | | -8j=-9-9j | | -1x+2=2x-2 | | 7-4w=-6w-3 | | -104=-8n+4(-5-n) | | 39.72-7.6n=0.8(n-6) | | -6-7=-7f | | 3(-7+4r)=-93 | | (2x+9)*2=3x+35 | | 2p-9=-7p | | (3x+35)/2=(2x+9) | | -8(-3x+6)=-120 | | v+1/5=13/5+7v | | -d=8-2d | | -8-8m=-6m | | h−12=54 | | -4^3+84^2+432x+250=0 | | f+4/2=10 | | -8(3+7x)=200 | | (2x+9)=(3x+35)/2 | | -2-n=-5-2n | | s+13.5=17 | | 7v+2(7v-2)=-172 |